Women’s Language in the Movie Script of The Perks of being a Wallflower - Kurniaty, Nunung (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p37, 2018)
This study entitled Women’s Languange in the movie script of The Perks of Being a  Wallflower . This study is aimed at identifying the language features applied by women and finding out the functions of the language in the movie script.The theories applied in this study were the theory of women’s language proposed by lakoff (1975). Lakoff states that women’s speech was characterized by language features such as: the use hedges and fillers, tag question, rising or question intonation, empty adjective, precise color, intensifier, hypercorrect grammar, super polite form, the avoidance strong swear word, and emphatic stress. This study used the movie script of The Perks of Being a  Wallflower as the data source. The movie script was choosen as the data in this study because it contained women’s language. The collected data were selected and put into categories of women’s language features and their functions which were descriptively analyzed based on the theory applied.The finding of analysis shows that the women’s language features found in this movie script include the use lexical hedges, tag question, rising or question intonation, empty adjective, intensifier, hypercorrect grammar, super polite form, and the avoidance strong swear word. Morever, the findings also show that the function of the women’s language features show the speaker’s strengthened assertion, the speaker’s admiration for something, and to emphasize the speaker’s judgment of something.